A comprehensive approach to metastasis in the oral and maxillofacial region: a narrative review - Rodríguez-Mora , Juan Pablo; Peña-Vega, Claudia Patricia (Journal of Oral Diagnosis, 2025)
According to the latest Head and Neck Tumor Classification by the World Health Organization (WHO, 2022), metastases to the oral and maxillofacial region (OMFR) are rare, accounting for less than 1% of all neoplasms reported in this area. These lesions are more prevalent in adults between the sixth and seventh decades of life, with a survival rate of less than one year in 90% of cases, reflecting their high morbidity and mortality. Due to the absence of pathognomonic clinical, radiographic, and histopathological features, metastases in the OMFR present a significant diagnostic challenge. Immunohistochemical studies are essential for identifying the primary tumor in cases of unknown origin. This narrative review aims to describe the main clinical, radiographic, histopathological, and immunohistochemical characteristics of metastatic tumors in the OMFR, emphasizing the need for a comprehensive and multidisciplinary diagnostic approach to ensure accurate identification and timely management.